PRACOWNIK SKIEROWANY NA NAUKĘ A PRACOWNIK PODEJMUJĄCY NAUKĘ Z WŁASNEJ INICJATYWY - Pogorzelska, Dorota (Wydział Prawa i Administracji UAM, 2002)
The aim of this article is to present the current range of benefits available for employees raising their professional qualifications with and without reference from the employer. The Author compares in this respect the previous Resolution of Council of Ministers No 263 of 23rd December 1982 with the regulations currently in force, especially the Resolution of the National Education Ministry and the Ministry of Labour and Social Policy of 12th October 1993. A thorough analysis is made of the particular obligations, concessions, and limitations that are at present in force and that apply to persons raising their professional qualifications. The Author arrives at the conclusion that these legal issues need to be fine-tuned and standardized.
EMPLOYEE DIRECTED TO TAKE UP STUDIES AND EMPLOYEE BEGINNING STUDIES AT HIS OWN INITIATIVE